The Effect of Health Education During the Covid 19 Period on Increasing Knowledge in Comorbid Patients (Suspected) With Diabetes Mellitus (DM) At Harum Sisma Medika Hospital, Jakarta 2021 - Rogayah; Al-Bahra (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2021)
The purpose of this study was to determine the effect of health education during the Covid 19 period on increasing knowledge in comorbid (suspected) patients with Diabetes Mellitus (DM) at Harum Sisma Medika Hospital, Jakarta. This study uses a quantitative approach with a pre-experimental research design, one group pre-post test design. The sample in this study was 18 respondents who were selected by purposive sampling technique. The study took place in the isolation ward of the Harum Sisma Medika Hospital, Jakarta. The instrument used is the DKQ-24 questionnaire (Diabetes Knowledge Questionnaire) with 24 question items. The test is a paired t test. The results showed that there was a difference in the mean score between knowledge before and after health education with the p value before and after being given health education related to covid 19, namely 0.002 (P <0.05). Factors significantly associated with preventive behaviour are knowledge and education. Knowledge related to COVID-19 prevention behaviour is carried out by wearing masks, maintaining hand hygiene, and avoiding crowds. In a study of diabetic and nondiabetic patients, diabetic patients expressed concern about the risk of COVID19 infection. They changed behaviour and lifestyle due to the COVID-19 pandemic. Knowledge and attitudes are associated with COVID-19 prevention behaviour.